Perbedaan Prestasi Akademik Mahasiswa Politeknik Kesehatan Kemenkes Semarang Berdasarkan Jalur Masuk pada Seleksi Penerimaan Mahasiswa Baru - Warijan Warijan; Hermien Nugraheni; Anton Kristijono (Jurnal LINK, 2013)
Entrance Path selection for admission of new students was held at the Ministry of Health Polytechnic Semarang is a search path Interests and Achievements (PMDP), Public paths or Test Write conducted nationally and Independent lines. Patterns and selection methods designed to get raw input excel not only in academics but also has the potential to expand the institution, so it will be candidates qualified health workers to support health care.The purpose of this study was to identify differences in Academic Achievement’s Student of Health Polytechnic Ministry of Health Semarang Based on Entrance Paths in Selection Admissions (Sipenmaru).The selected type of research is explanatory research with cross sectional design, this study will illustrate the correlation between the independent factors and the dependent, by way of approach, observation or data collection at once at a time.Univariate test results showed polytechnic students Ministry of Health Semarang most received through General (written test) in Sipenmaru, derived from the high school, and academic achievement is very satisfying. While the results of the test pair t-test showed that students' academic achievement Ministry of Health Semarang Polytechnic high average student entry through PMDP in Sipenmaru and coming from high school.